Abnormal grain growth in high speed steels. (September 2013) - Schemmel, I.; Martinschitz, Ch.; Leitner, H.; Kellezi, G.
Abstract : The combination of the chemical composition and a specific heat treatment consisting of austenitising close to solidus temperature and subsequent triple tempering leads to the excellent properties of high speed steels. Usually when high speed steels are heated up to austenitising temperature, intermediate holding stages and specific heating rates are applied. This specific heat treatment affects the microstructure, especially the grain size distribution. In some cases, abnormal grain growth can occur. This study describes the influence of the variation of the parameters, such as intermediate holding temperature and heating rate on the microstructural development. All investigations were carried out on the high speed steel HS 6-5-2-5 using both laboratory tests and vacuum heat treating.